Polymorphisms of the ADAM33 gene are associated with accelerated lung function decline in asthma - Jongepier, H.; Boezen, H. M.; Dijkstra, A.; Howard, T. D.; Vonk, J. M.; Koppelman, G. H.; Zheng, S. L.; Meyers, D. A.; Bleecker, E. R.; Postma, D. S. (Clinical and experimental allergy, 2004)
Summary Background Asthma is a genetically complex disease characterized by respiratory symptoms, intermittent airway obstruction and airway hyper‐responsiveness due to airway inflammation and remodelling. The ADAM33 gene is associated with asthma and airway hyper‐responsiveness and is postulated as a gene for airway remodelling. Objective To investigate whether polymorphisms of the ADAM33 gene are associated with accelerated lung function decline in patients with asthma. Methods In a cohort of 200 asthma patients followed over 20 years, eight single nucleotide polymorphisms of the ADAM33 gene were analysed to estimate their effect on annual FEV1 decline. Results The rare allele of the S_2 polymorphism was significantly associated with excess decline in FEV1 (P<0.05). Conclusion These findings suggest that a variant in ADAM33 is not only important in the development of asthma but also in disease progression, possibly related to enhanced airway remodelling.